Hitherto Unreported Macrofungi From Jammu & Kashmir - Ii (Applied Biological Research, 2010)
The Jammu & Kashmir State, lying on the Western Himalayas harbours rich  biodiversity in macrofungi owing to peculiar physiography and wide variation  in agro-climatic conditions. During the survey of mycorrhizae prevailing in  conifer-dominated forests of Kashmir four hitherto un-reported macrofungi  viz, Bolbitius vitellinus (Pers.: Fries) Fries, Clitocybe nuda (Bull.:Fr.) Bigelow & Smith, Coprinopsis macrocephala (Berk.) Berk.Stroh-Tintling and Tricholoma scalpturatum (Fr.) Quél. were collected. These are reported for the  first time from the Jammu & Kashmir State, India.
Keywords: Bolbitius vitellinus; Clitocybe nuda; Coprinopsis macrocephala; forests; India; Jammu & Kashmir; macrofungi; Tricholoma scalpturatum